Characterization of three new SERPINA1 variants PiQ0Heidelberg II, PiQ0Heidelberg III and PiQ0Heidelberg IV in patients with severe alpha-1 antitrypsin deficiency. (2023) - Höger, Philipp; Veith, Martina; Greulich, Timm; Limen, Eldridge; Brock, Judith; Schlamp, Kai; Buschulte, Katharina; Presotto, Maria A.; Schäfer, Julia Carmen; Herth, Felix; Trudzinski, Franziska C.
Abstract: Background: The clinical and molecular characteristics of three patients with previously unreported SERPINA1 mutations associated with severe alpha-1 antitrypsin deficiency (AATD) are described. The pathophysiology of the chronic obstructive pulmonary disease (COPD) present in these patients was characterized through clinical, biochemical, and genetic examinations. Case presentations: Case 1: A 73-year-old male with bilateral centri-to panlobular emphysema and multiple increasing ventrobasal bullae and incomplete fissures, COPD (Global Initiative for Chronic Obstructive Lung Disease (GOLD) grade III B), progressive dyspnea on exertion (DOE), AAT level of 0.1–0.2 g/L. Genetic testing revealed a unique SERPINA1 mutation: Pi*Z/c.1072C > T. This allele was designated PiQ0Heidelberg II . Case 2: A 47-year-old male with severely heterogenous centri-to panlobular emphysema concentrated in the lower lobes, COPD GOLD IV D with progressive DOE, AAT <0.1 g/L. He also had a unique Pi*Z/c.10del mutation in SERPINA1 . This allele was named PiQ0Heidelberg III . Case 3: A 58-year-old female with basally accentuated panlobular emphysema, GOLD II B COPD, progressive DOE. AAT 0.1 g/L. Genetic analysis revealed Pi*Z/c.-5+1G > A and c.-472G > A mutations in SERPINA1 . This variant allele was named PiQ0Heidelberg IV . Conclusions: Each of these patients had a unique and previously unreported SERPINA1 mutation. In two cases, AATD and a history of smoking led to severe lung disease. In the third case, timely diagnosis, and institution of AAT replacement stabilized lung function. Wider screening of COPD patients for AATD could lead to faster diagnosis and earlier treatment of AATD patients with AATD which could slow or prevent progression of their disease. Highlights: Three patients with COPD were found to have unique variants of SERPINA1 resulting in severe alpha-1 antitrypsin deficiency. A patient with less severe disease at diagnosis was treated with AAT augmentation and achieved stable pulmonary function. More research is warranted to assess whether earlier diagnosis of and therapy for AAT deficiency can improve outcomes.